2009
DOI: 10.1097/wnr.0b013e32832e0cc1
|View full text |Cite
|
Sign up to set email alerts
|

Modality-specific hyperexcitability of dorsal horn neurons to mechanical stimuli in herpetic mice

Abstract: Percutaneous inoculation of mice with herpes simplex virus type-1 produces marked dynamic allodynia in the zosteriform dermatome. In this study, we examined the electrophysiological excitability of the wide-dynamic range neuron in the spinal dorsal horn and the tibial nerve in response to mechanical (brush, punctum, and pinch) stimuli in mice with herpetic allodynia. The excitatory response of wide-dynamic range neurons to brush, but neither punctum nor pinch, stimulation of the zosteriform dermatome was incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Our recent study has demonstrated that the excitatory response of spinal dorsal horn neurons to brush stimulation of the lesional skin was increased in herpetic mice, while the response of the tibial nerve, a branch of the sciatic nerve innervating the affected skin, to brush stimulation was decreased (11). These findings suggest that dynamic allodynia in the affected dermatome is due to the increased excitability of spinal dorsal horn neurons, but not primary afferents, to brush stimulation.…”
Section: Introductionmentioning
confidence: 73%
“…Our recent study has demonstrated that the excitatory response of spinal dorsal horn neurons to brush stimulation of the lesional skin was increased in herpetic mice, while the response of the tibial nerve, a branch of the sciatic nerve innervating the affected skin, to brush stimulation was decreased (11). These findings suggest that dynamic allodynia in the affected dermatome is due to the increased excitability of spinal dorsal horn neurons, but not primary afferents, to brush stimulation.…”
Section: Introductionmentioning
confidence: 73%